Urban Nighttime Heat Island Effect Monitoring Based on DMSP/OLS and MODIS Data - Wang, Kun (International Journal of Computer Science and Information Technology, 2024)
The urban heat island effect has become a hot issue of current scientific research, Anhui Province is in the eastern zone of China, since the reform and opening up, in the city of the building area of the non-stop expansion at the same time, the heat island effect of the city of Anhui Province is becoming more and more obvious, so quantitative research on the response relationship between nighttime lighting intensity and the city's nighttime temperature, to rationally plan the construction of the city to further alleviate and control the urban heat island to provide a scientific basis. In this paper, we use MOD11A1 data from MODIS data covering Anhui Province in 2013 to calculate the nighttime surface temperature, and since the value of NDBI is larger as it goes to the city center, we use this characteristic to construct the nighttime lighting index (NLI) based on NDBI, and then we extract the built-up areas of 16 cities in Anhui Province, and the accuracy of the extractions are all above 90%. The nighttime lighting index and the nighttime surface temperature of the built-up areas of each city were analyzed to establish a regression equation, and the nighttime surface temperature of the built-up areas of each city was obtained by inversion through the regression equation, and finally the nighttime heat island index NHII was calculated. The results show that the nighttime heat island level of the cities in the north of Anhui Province is generally higher than that in the south of Anhui Province, and that of the cities in the middle of Anhui Province is higher than that of the surrounding cities.